Komodifikasi Bahasa dan Citra Usaha: Kajian Lanskap Linguistik Kuliner di Kota Pamekasan - Titik Wahyuni; Teguh Setiawan; Wiyatmi Wiyatmi (Universitas Nahdlatul Wathan Mataram, 2026)
The intense competition in the industrial sector is driving a shift in the function of language use in the public sphere. As a means of communication, the linguistic landscape plays a crucial role in connecting business owners and consumers. This study aims to examine the commodification of language in the culinary linguistic landscape in Pamekasan City, encompassing the forms of language use, commodification practices, and their implications for the formation of business image. This study uses a qualitative approach with descriptive methods. Data were obtained through observation, documentation, and note-taking techniques. Then, they were analyzed using an interactive analysis model consisting of data condensation, data presentation, and conclusion drawing. The results show that language use in the culinary linguistic landscape consists of monolingual, bilingual, and multilingual forms with variations in the use of Madurese, Indonesian, English, Arabic, and Javanese. The dominance of Madurese indicates a very strong local identity for the Pamekasan community. Furthermore, there is clear evidence of language commodification, demonstrated through the use of language in LL as a commercial attraction, shaping consumer perceptions, and a symbol of business differentiation. This has implications for the formation of a business image, such as a modern, religious, friendly, unique, and authentic impression. Thus, the linguistic landscape serves not only as an information medium but also as a strategic tool for building the economic value and identity of culinary businesses in the public sphere.